2004
DOI: 10.1128/aem.70.12.7126-7139.2004
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Approach to the Problem of Hybridization Efficiency in Fluorescent In Situ Hybridization

Abstract: In fluorescent in situ hybridization (FISH), the efficiency of hybridization between the DNA probe and the rRNA has been related to the accessibility of the rRNA when ribosome content and cell permeability are not limiting. Published rRNA accessibility maps show that probe brightness is sensitive to the organism being hybridized and the exact location of the target site and, hence, it is highly unpredictable based on accessibility only. In this study, a model of FISH based on the thermodynamics of nucleic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
138
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(141 citation statements)
references
References 38 publications
3
138
0
Order By: Relevance
“…For samples analyzed after the CAR-108 cruise, we replaced EPS549 with EPS682 due to higher hybridization efficiency of EPS682 (Gibbs free energy change 5 212.5 kcal mol 21 ) compared with EPS549 (Gibbs free energy change 5 29.0 kcal mol 21 ). Gibbs free energy change is a proxy for probe hybridization efficiency and was calculated according to Yilmaz and Noguera (2004). Usually, a threshold value of 213.0 kcal mol 21 Gibbs free energy change is recommended for effective probe hybridization.…”
Section: Methodsmentioning
confidence: 99%
“…For samples analyzed after the CAR-108 cruise, we replaced EPS549 with EPS682 due to higher hybridization efficiency of EPS682 (Gibbs free energy change 5 212.5 kcal mol 21 ) compared with EPS549 (Gibbs free energy change 5 29.0 kcal mol 21 ). Gibbs free energy change is a proxy for probe hybridization efficiency and was calculated according to Yilmaz and Noguera (2004). Usually, a threshold value of 213.0 kcal mol 21 Gibbs free energy change is recommended for effective probe hybridization.…”
Section: Methodsmentioning
confidence: 99%
“…While studies addressing the significance of the former factor in FISH have just started (5), the latter factor has been investigated extensively (7,(16)(17)(18)(19)50). The ability of probes to reach their target sites within the three-dimensional structure of the ribosome has been regarded as the major factor for hybridization efficiency (3).…”
mentioning
confidence: 99%
“…Amann et al (1995) reported that 23S rRNA was often used as a hybridization target molecule, because its sequences showed higher phylogenetic specificity than 16S rRNA sequences. Yilmaz and Noguera (2004) reported that fluorescence intensity was negatively correlated to the Gibbs free energy change (ΔG) in hybridization between the DNA probe and rRNA. Sawabe et al (2009) showed that greater brightness from the hybridized probes was obtained when V. parahaemolyticus was hybridized with probes in which ΔG ranged from −17 to −22; therefore, SAL343 was designed accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…The oligonucleotide probe was optimized for Gibbs's free energy of DNA-RNA hybridization (Yilmaz and Noguera, 2004 Alexa 488 ® ) and images were captured using a digital camera D50 (Nikon). Micro-colony diameter was determined from digital images using ImageJ ver.…”
Section: Methodsmentioning
confidence: 99%